Symbolic Interactionist Communication of Interreligious Figures in Managing Religious Diversity - Prasetya, Dimas; Prayogi, Arditya; Umaroh, Khoirotul (Universitas Muhammadiyah Prof. DR. Hamka, 2024)
This research aims to dissect interfaith figures’ symbolic interactionist communication approach in managing religious diversity. Using qualitative ethnographic research, data collection methods in the research used interviews, observation, and documentation. Listed as key informants were ten interfaith figures who were members of the Pekalongan City Religious Harmony Forum (FKUB). The research results show that interfaith figures in Pekalongan City use a symbolic interactionist communication approach in managing religious diversity in Pekalongan City. Among the forms of Symbolic Interactionism are symbols, gestures, language, rituals, education, and intercultural dialogue. The symbolic interactionism approach is also used to support the process of institutionalizing multicultural values which are the foundation for realizing religious harmony in Pekalongan City.